2016
DOI: 10.1177/2329488415572789
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Perceived Listening Behavior Differences Between Managers and Nonmanagers Living in the United States, India, and Malaysia

Abstract: Many managers and employees work in multinational organizations, but know little about what constitutes good or bad listening skills from a cross-cultural perspective. Little literature exists concerning the listening behaviors of managers and nonmanagers or the impact of national culture on listening skills. No clear understanding of what constitutes effective and ineffective listening across various cultures and organizational positions is known. Therefore, this study examines the listening skills of both ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Roebuck et al [14] found that the national culture is a primary determinant of communication behaviors, in particular with respect to listening. Listeners from high-context cultures, such as India and Malaysia, are more likely to respond to their gut-level reaction (the implicit message) than to the actual facts in the message.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roebuck et al [14] found that the national culture is a primary determinant of communication behaviors, in particular with respect to listening. Listeners from high-context cultures, such as India and Malaysia, are more likely to respond to their gut-level reaction (the implicit message) than to the actual facts in the message.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…The authors argue that managers who listen effectively benefit not only their employees but also all stakeholders within and outside an organization. Moreover, Roebuck et al [14] state that: as organizational structures become flatter (i.e., decreased power distance) managerial roles will focus more on coaching and collaboration, activities in which listening skills will be essential to achieving individual, team, and organizational goals hinting that communication skills manifested in low-context cultures, and lower power distance come hand-in-hand, and they can decrease the risks of project failure. This supports our finding that good client countries were low on power distance, high on individualism and using a low-context communication style.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Ramos Salazar (2017) distinguished between content listening (focusing on facts and figures) and people listening (focusing on feelings and emotions), arguing that only the latter relates to compassion. Roebuck et al (2015) investigated four types of listening behaviors of managers and nonmanagers—empathetic listening, distracted listening, judgment rushing, and conclusion jumping—claiming that the latter three types reflect a view on listening as a waste of time, with many potentially negative consequences. Golen (1990) identified six listening barriers, which can be seen as immediate threats to empathic behavior: being lazy, closed-minded, opiniated, insincere, bored, and inattentive.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Empathy has been found to be an asset during negotiations and to increase creativity in teams, enhance cooperation, raise employee commitment, and strengthen leadership abilities (Carmeli, 2003; Galinski et al, 2008; Gentry et al, 2010; Hoever et al, 2012; Morelli et al, 2014; Ruderman et al, 2001). It is especially crucial for professionals working in intercultural settings, conducting difficult workplace conversations, or working in turbulent environments such as organizations in times of crisis (Alon & Higgins, 2005; Bradley & Campbell, 2016; Claeys et al, 2013; Roebuck et al, 2016). But even in routinely short-term interactions between customers and call centers, empathy plays an important role (Clark et al, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%